A Systematic Account on Aromatic Hydroxylation by a Cytochrome P450 Model Compound I: A Low‐Pressure Mass Spectrometry and Computational Study. Issue 51 (15th November 2016) - Cantú Reinhard, Fabián G.; Sainna, Mala A.; Upadhyay, Pranav; Balan, G. Alex; Kumar, Devesh; Fornarini, Simonetta; Crestoni, Maria Elisa; de Visser, Sam P.
Abstract: Cytochrome P450 enzymes are heme‐containing mono‐oxygenases that mainly react through oxygen‐atom transfer. Specific features of substrate and oxidant that determine the reaction rate constant for oxygen atom transfer are still poorly understood and therefore, we did a systematic gas‐phase study on reactions by iron(IV)‐oxo porphyrin cation radical structures with arenes. We present herein the first results obtained by using Fourier transform‐ion cyclotron resonance mass spectrometry and provide rate constants and product distributions for the assayed reactions. Product distributions and kinetic isotope effect studies implicate a rate‐determining aromatic hydroxylation reaction that correlates with the ionization energy of the substrate and no evidence of aliphatic hydroxylation products is observed. To further understand the details of the reaction mechanism, a computational study on a model complex was performed. These studies confirm the experimental hypothesis of dominant aromatic over aliphatic hydroxylation and show that the lack of an axial ligand affects the aliphatic pathways. Moreover, a two‐parabola valence bond model is used to rationalize the rate constant and identify key properties of the oxidant and substrate that drive the reaction. In particular, the work shows that aromatic hydroxylation rates correlate with the ionization energy of the substrate as well as with the electron affinity of the oxidant. Abstract : How does it work? A combined mass spectrometry and density functional theory study on aromatic hydroxylation by a cytochrome P450 Compound I model is presented. Details of the mechanism are elucidated from kinetics, isotope effects, and computational studies and show that the rate constant correlates with the ionization energy of the oxidant.